Synthesis and characterization of two-dimensional (2D) nanosheet zinc aluminum layered double hydroxide (Zn/Al LDH) via an alkali-free route / Rabiatul Adawiyah Mohd Agus, Siti Khatijah Deraman and Nazrizawati A. Tajuddin - Mohd Agus, Rabiatul Adawiyah; Deraman, Siti Khatijah; A. Tajuddin, Nazrizawati (Faculty of Applied Sciences, 2021)
The effect of different molar ratios on the synthesis of zinc aluminium layered double hydroxide (Zn/Al LDH) via an alkali-free route was carried out in this research. This method was prepared by mixing zinc nitrate solution, aluminium nitrate solution, and ammonium carbonate solution at a constant pH of 8.5 with a spanning ratio of Zn to Al from 4:1, 3:1, and 2:1. The XRD patterns showed crystal nanostructure of Zn/Al LDHs was successfully formed. The lattice parameters (a and c) were slightly increased with the increasing of Zn/Al molar ratio. A larger hexagonal platelet is observed in the SEM image align with the high molar ratio of Zn/Al synthesized. The same trend has been observed in the FTIR spectra.